Influence of organic ions on DNA damage induced by 1 eV to 60 keV electrons - Zheng, Yi (2010)
We report the results of a study on the influence of organic salts on the induction of single strand breaks (SSBs) and double strand breaks (DSBs) in DNA by electrons of 1 eV to 60 keV. Plasmid DNA films are prepared with two different concentrations of organic salts, by varying the amount of the TE buffer (Tris-HCl and EDTA) in the films with ratio of 1:1 and 6:1 Tris ions to DNA nucleotide. The films are bombarded with electrons of 1, 10, 100, and 60 000 eV under vacuum. The damage to the 3197 base-pair plasmid is analyzed ex vacuo by agarose gel electrophoresis. The highest yields are reached at 100 eV and the lowest ones at 60 keV. The ratios of SSB to DSB are surprisingly low at 10 eV (~4.3) at both salt concentrations, and comparable to the ratios measured with 100 eV electrons. At all characteristic electron energies, the yields of SSB and DSB are found to be higher for the DNA having the lowest salt concentration. However, the organic salts are more efficient at protecting DNA against the damage induced by 1 and 10 eV electrons. DNA damage and protection by organic ions are discussed in terms of mechanisms operative at each electron energy. It is suggested that these ions create additional electric fields within the groove of DNA, which modify the resonance parameter of 1 and 10 eV electrons, namely, by reducing the electron capture cross-section of basic DNA units and the lifetime of corresponding transient anions. An interstrand electron transfer mechanism is proposed to explain the low ratios for the yields of SSB to those of DSB produced by 10 eV electrons.